2019
DOI: 10.2967/jnumed.118.224543
|View full text |Cite
|
Sign up to set email alerts
|

Intention-to-Treat Analysis of 68Ga-PSMA and 11C-Choline PET/CT Versus CT for Prostate Cancer Recurrence After Surgery

Abstract: Biochemical recurrence (BCR) after prostate cancer surgery is common, even after additional salvage radiotherapy. BCR might be explained by target miss. Improved diagnostic accuracy provided by PET could potentially circumvent this therapeutic gap. Therefore, we evaluated consecutive 68 Ga-prostate-specific membrane antigen (PSMA) PET/CT, 11 C-choline PET/CT, and standard CT imaging in the same patient with regard to TNM-stage migration and accordingly adapted curative radiotherapy options including ablative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
18
1
Order By: Relevance
“…Despite the differences in the findings of the two modalities, TNM staging and subsequent patient management was not affected in the majority of patients in the current study (86%; Table 3). This contrasts the findings observed by Schwenck et al They reported a 50% change in patients management using [ 68 Ga]Ga-PSMA as opposed to [ 18 F]Fluorocholine for PET/CT in biochemical recurrence stage [37].…”
Section: Discussioncontrasting
confidence: 84%
“…Despite the differences in the findings of the two modalities, TNM staging and subsequent patient management was not affected in the majority of patients in the current study (86%; Table 3). This contrasts the findings observed by Schwenck et al They reported a 50% change in patients management using [ 68 Ga]Ga-PSMA as opposed to [ 18 F]Fluorocholine for PET/CT in biochemical recurrence stage [37].…”
Section: Discussioncontrasting
confidence: 84%
“…In these cases, early detection and localization of recurrent disease is crucial for further disease management [4,5]. Conventional imaging such as computed tomography (CT) or magnetic resonance imaging as well as choline-based PET often fails to localize biochemical recurrence [4,[6][7][8]. Since its first introduction in 2014, 68 Ga-PSMA-11-ligand positron emission tomography/computed tomography (PET/CT) has been adopted rapidly around the world given its high sensitivity and specificity for the detection and localization PC lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding detection rate of another PET-tracer, 68 Ga-PSMA identified significantly higher number of PET-positive lesions compared to 11 C-choline [14]. Furthermore, 68 Ga-PSMA-PET/CT demonstrated an improved cost efficacy with a number needed to image of 2 compared to 4 with 11 C-choline PET/CT [21]. Improved accuracy of 68 Ga-PSMA was also substantiated by a previously performed meta-analysis [22,23] especially for BCR after RP with PSA-levels below 1.0 ng/mL [24].…”
Section: Discussionmentioning
confidence: 91%